Hubungan parental stress terhadap self-esteem orang tua yang memiliki anak dengan autism spectrum disorder - Magdhalena, Widya; Hariyono, Dyta Setiawati (Universitas Muhammadiyah Malang, 2023)
Parents of children with ASD (Autism Spectrum Disorder) face challenges that put them at high levels of stress. Self- esteem can reduce the negative impact of parental stress. The aim of this research is to analyze the relationship between parental stress and self-esteem in parents who have children with ASD. The method used in this research uses quantitative methods with a correlational design. The sample for this study was 114 parents with ASD. Parental stress was measured using the Parental Stress Scale (PSS) and self-esteem was measured using the self-esteem scale. Pearson product moment correlation was used to analyze the data. The results of the Pearson product moment test obtained r = -.46 and p = 0.00. The results of this study found that parents had moderate levels of parental stress (69.3%) and had moderate self-esteem (60.5%). These results prove that there is a significant relationship between parental stress and self-esteem in ASD parentsKeywords: Autism Spectrum Disorder, parental stress, self-esteem